Estetická interpretace lásky a smrti se zřetelem k dílům Hölderlina a Rilka - Roreček, Eduard; Střítecký, Jaroslav, 1941-; Masarykova univerzita. Seminář estetiky (2008)
V první části usiluje práce o přiblížení lásky a smrti v proměnách evropské kultury a její literární tradice. Pokouší se také o estetickou kategorizaci těchto pojmů. U Hölderlina poukazuje na napětí mezi antikou a křesťanstvím a zdůrazňuje roli řeckého antického ideálu. Lásku chápe Hölderlin ve spojení s krásou a nesmrtelností. V Rilkově díle představuje klíčové prvky model velké a malé smrti, zrající smrti a intranzitivní lásky. Zásadní vliv je přisouzen Rilkově gnosticismu. Oba autory spojuje použití mýtických prvků, dionýského principu, inklinace k panteismu, dialektičnost a hluboké významové přesahy. Závěr práce se zamýšlí nad láskou jako hermeneutickým principem s odkazem na Schelerovu koncepci ordo amoris
The first part of this work makes an effort to explain how love and death were changing in European culture and its literary tradition. The disertation is also attempting to categorize aesthetically these ideas. The part of Hölderlin is poiting out to tension between antique and Christianism, underlining function of Greek classical ideal. Hölderlin understands love in conjunction with beauty and immortality. In Rilke's work, main points are forms of "big, small and maturing death“ and „intransitive love". The most important thing is Rilke's gnosticism. Both authors are connected by using mythic items, Dyonisian principle, tending to pantheism, dialectics and trancendental overlap. At the end of my work is love understood as hermeneutic principle reffering to Scheler's conception ordo amoris. Scheler's term "act of love" is used as a solution of hermeneutic approach to an interpretation. Every understanding (especially understanding of literary text) can be translated as the "act of l
Vedoucí práce: Jaroslav Střítecký
Dizertace (Ph.D.)--Masarykova univerzita, Filozofická fakulta, 2008
Keywords: disertace; dissertations